Cumprimento de sentença: eficácia executiva derivada de sentença condenatória - Rostagno, Alessandro (2007)
The present work has for objective to analyze the juridical nature of the cognitive decision that allows to open the denominated procedural moment of 'sentence execution', in the right brazilian civil procedure, in agreement with the innovations brought by the law n. 11.232/05, that had for presupposition, to allow a larger procedural effectiveness and procedimental concerning the execution of the obligations recognized in sentence that determine the payment of amount. It is looked for, through the study of the historical sources, of comparative right and of the classification of the sentences, and the combination of the effectiveness of the jurisdictional decisions, to obtain conclusion concerning that type of effects will be found in the practical performance of the law that disposes concerning the sentence execution and, above all, as if it executes the conduct of the parts and judge before the procedure imposed by the legal text to the brazilian civil procedural system